IMPROVING STUDENTS’ CRITICAL THINKING SKILLS ON HYDROCARBON MATERIAL THROUGH ASSESSMENT FOR LEARNING - Adam Al Halwi; Muchlis Muchlis (Jurnal Eduscience, 2025)
Purpose–This study describes the effectiveness of implementing the Assessment for Learning (AfL) approach to improve students' critical thinking skills on hydrocarbon materials.